FACTORS INFLUENCING THE ADOPTION OF EMERGING TECHNOLOGIES BY INDIGENOUS CONSTRUCTION AND REAL ESTATE DEVELOPMENT COMPANIES IN ABUJA, NIGERIA - Wendy, Ogheneyoma Chima; UDOEKANEM, Namnso Bassey (Journal of Surveying, Construction and Property, 2024)
The aim of this paper is to assess the adoption of emerging technologies (ET) by indigenous construction and real estate development companies (CRED) in Abuja, Nigeria with a view to identifying the key driving factors. The study adopted a combination of descriptive and exploratory research designs. Data were collected through structured questionnaire administered to thirty - eight indigenous CRED companies in the study area via purposive sampling technique. Data obtained for the study were analysed through descriptive and inferential statistical techniques. The study found that drone technology is the most commonly used form of ET by indigenous CRED companies in Abuja with 26% of the total occurrence observed. This is followed by BIM (23%) and virtual reality (19%) respectively. It also found that location of the project, labour factor, government policy and technical nature of the project are the crucial factors that influence the adoption of ET by indigenous CRED companies in the study area. The study concludes that there are prospects of greater usage of ET by indigenous CRED companies for their operations in the city in the nearest future. In the light of the findings, it recommends the establishment of a robust regulatory framework by policy makers in the construction industry to clearly provide the technical and ethical standards required for the use of ET in the industry and the penalties for non-compliance especially concerning geographical coverage, data privacy and data security.